Bread Enriched With Legume Microgreens and Leaves—Ontogenetic and Baking-Driven Changes in the Profile of Secondary Plant Metabolites - Klopsch, Rebecca; Baldermann, Susanne; Voss, Alexander; Rohn, Sascha; Schreiner, Monika; Neugart, Susanne (Frontiers in Chemistry, 2018)
Flavonoids, carotenoids, and chlorophylls were characterized in microgreens and leaves of pea (Pisum sativum) and lupin (Lupinus angustifolius) as these metabolites change during ontogeny. All metabolites were higher in the leaves for both species. Acylated quercetin and kaempferol sophorotrioses were predominant in pea. Genistein and malonylated chrysoeriol were predominant in lupin. Further, the impact of bread making on these metabolites using pea and lupin material of two ontogenetic stages as an added ingredient in wheat-based bread was assessed. In ‘pea microgreen bread’ no decrease of quercetin was found with regard to the non-processed plant material. However kaempferol glycosides showed slight decreases induced by the bread making process in ‘pea microgreen bread’ and ‘pea leaf bread’. In ‘lupin microgreen bread’ no decrease of genistein compared to the non-processed plant material was found. Chrysoeriol glycosides showed slight decreases induced by the bread making process in ‘lupin microgreen bread’ and ‘lupin leaf bread’. In all breads, carotenoids and chlorophylls were depleted and pheophytin formation was caused. Thus, pea and lupin microgreens and leaves are suitable, natural ingredients for enhancing health-promoting secondary plant metabolites in bread and may even be used to tailor bread for specific consumer health needs.